Cardiovascular and Metabolic Responses to the Ingestion of Caffeinated Herbal Tea: Drink It Hot or Cold? - Maufrais, Claire; Sarafian, Delphine; Dulloo, Abdul; Montani, Jean-Pierre (Frontiers in Physiology, 2018)
Aim. Tea is usually consumed at two temperatures (as hot tea or as iced tea). However, the importance of drink temperature on the cardiovascular system and on metabolism has not been thoroughly investigated. The purpose of this study was to compare the cardiovascular and metabolic and cutaneous response to the ingestion of caffeinated herbal tea (Yerba Mate) at cold or hot temperature in healthy young subjects. We hypothesized that ingestion of cold tea induces a higher increase in energy expenditure than hot tea without eliciting any negative effects on the cardiovascular system. Methods. Cardiovascular, metabolic and cutaneous responses were analyzed in twenty-three healthy subjects (twelve men and eleven women) sitting comfortably with a 30-min baseline and 90 min following the ingestion of 500 mL of an unsweetened Yerba Mate tea ingested over 5 min either at cold (~3 °C) or hot (~55 °C) temperature, according to a randomized cross-over design. Results. Averaged over the 90 min post-drink ingestion and compared to hot tea, cold tea induced 1) a decrease in heart rate (cold tea: -5 ± 1 beats.min-1; hot tea: -1 ± 1 beats.min-1, p<0.05), double product, skin blood flow and hand temperature and 2) an increase in baroreflex sensitivity, fat oxidation and energy expenditure (cold tea: +8.3 %; hot tea: +3.7 %, p<0.05). Averaged over the 90 min post-drink ingestion, we observed no differences in tea temperature on cardiac output work and mean blood pressure responses. Conclusion. Ingestion of an unsweetened caffeinated herbal tea at cold temperature induced a greater stimulation of thermogenesis and fat oxidation than hot tea while decreasing cardiac load as suggested by the decrease in the double product. Further experiments are needed to evaluate the clinical impact of unsweetened caffeinated herbal tea at a cold temperature for weight control.